An unidentified cluster of infection in the Peruvian Amazon region - Cornejo, A (2015)
Bartonella bacilliformis is the etiological agent of Carrion’s disease, which is a neglected disease linked to people in low-socioeconomic populations in Andean valleys. An outbreak of B. bacilliformis was reported in a rural area of the Peruvian Amazon region. The aim of this study was to characterize this outbreak using molecular techniques.